Speech Acts of Pangeuyeuks in Ngeuyeuk Seureuh Ceremony - Euis Kurniasih (Universitas Indraprasta PGRI, 2020)
Pangeuyeuks as the guide in Ngeuyeuk Seureuh ceremony has an important role to explain the marriage values through symbols to prospective bride and groom. This article describes speech acts used by pangeuyeuks in Ngeuyeuk Seureuh ceremony. Descriptive qualitative and distributional method was applied in doing the analysis of data. The speech acts were analyzed by the theory of illocutionary act to find the function of speech act, syntactic types of sentences to find the form of speech acts, and relationship between the function and form of speech acts to find the directness and indirectness of speech acts. The result shows that the illocutionary acts of pangeuyeuks classified into four types: assertives, directives, commissives and expressives, while the sytanctic types of sentences consist of declarative, interrogative, imperative and exclamatory. The direct speech acts are embodied in assertives, directives, commissives and expressives, wheareas the indirect speech acts are embodied in directive speech acts. The embodiment of the speech acts used by pangeuyeuks reflects special norms of interaction based on Sundanese local genius.